Numerical Analysis of Finite Dimensional Approximations in Finite Temperature DFT (CSIAM Transactions on Applied Mathematics, 2025)
In this paper, we study numerical approximations of the ground states infinite temperature density functional theory. We formulate the problem with respectto the density matrices and justify the convergence of the finite dimensional approximations. Moreover, we provide an optimal a priori error estimate under some mildassumptions and present some numerical experiments to support the theory.